Coffee extract and caffeine enhance the heat shock response and promote proteostasis in an HSF-1-dependent manner in Caenorhabditis elegans - Brunquell, Jessica (Cell Stress Chaperones, 2017)
As the population ages, there is a critical need to uncover strategies to combat diseases of aging. Studies in the soil-dwelling nematode Caenorhabditis elegans have demonstrated the protective effects of coffee extract and caffeine in promoting the induction of conserved longevity pathways including the insulin-like signaling pathway and the oxidative stress response. We were interested in determining the effects of coffee and caffeine treatment on the regulation of the heat shock response. The heat shock response is a highly conserved cellular response that functions as a cytoprotective mechanism during stress, mediated by the heat shock transcription factor HSF-1. In the worm, HSF-1 not only promotes protection against stress but is also essential for development and longevity. Induction of the heat shock response has been suggested to be beneficial for diseases of protein conformation by preventing protein misfolding and aggregation, and as such has been proposed as a therapeutic target for age-associated neurodegenerative disorders. In this study, we demonstrate that coffee is a potent, dose-dependent, inducer of the heat shock response. Treatment with a moderate dose of pure caffeine was also able to induce the heat shock response, indicating caffeine as an important component within coffee for producing this response. The effects that we observe with both coffee and pure caffeine on the heat shock response are both dependent on HSF-1. In a C. elegans Huntington’s disease model, worms treated with caffeine were protected from polyglutamine aggregates and toxicity, an effect that was also HSF-1-dependent. In conclusion, these results demonstrate caffeinated coffee, and pure caffeine, as protective substances that promote proteostasis through induction of the heat shock response. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12192-017-0824-7) contains supplementary material, which is available to authorized users.